2006
DOI: 10.1097/01.blo.0000188064.56091.a7
|View full text |Cite
|
Sign up to set email alerts
|

Second Application of Low-energy Shock Waves Has a Cumulative Effect on Free Nerve Endings

Abstract: Some physicians recommend treating tendinopathies with multiple sessions of shock waves. Some evidence, however, suggests shock wave application can induce nerve fiber degeneration. We questioned whether repeated shock wave application provides a cumulative effect on nerve fibers compared with the effect of one application. One thousand shock wave impulses of an energy flux density of 0.08 mJ/mm were applied to the foot pad of 32 rats. After 14 days, 16 rats received a second application. The foot pads were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 21 publications
4
62
0
1
Order By: Relevance
“…Currently, there are no standardized guidelines for the number of rESWT sessions required when treating soft tissue conditions,50 although studies have suggested that multiple applications provide superior long-term results compared with a single application 51. Compared to other tendinopathies treated with rESWT, the finger is a rather painful area to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no standardized guidelines for the number of rESWT sessions required when treating soft tissue conditions,50 although studies have suggested that multiple applications provide superior long-term results compared with a single application 51. Compared to other tendinopathies treated with rESWT, the finger is a rather painful area to treat.…”
Section: Discussionmentioning
confidence: 99%
“…The fibers began to regenerate in 14 days. By applying a second session of shock waves at 14 days, the nerve fiber regeneration was delayed to 42 days [175]. There is also evidence tenocytes release growth factors in response to ESWT that may promote tendon healing.…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%
“…Effects on soft tissues have been described as an early response involving activation of the sympathetic nerve endings and opening of the capillary bed (wash-out effect), and a secondary response, ensuing during the following days, leading to angiogenesis and removal of inflammatory mediators. A significant result of shock waves applied on soft tissues is the analgesic effect, which is due to action on nervous conduction (31), increase of free radicals that change nociceptors excitability, degeneration of nerve fibers that originate from small ATF3+ neurons, rapid degeneration of intracutaneous nerve fibers, and release of substance P (32). Several studies demonstrated the effectiveness of shock waves in promoting wound healing through the stimulation of many growth factors, such as EGF, IGF-l, VEGFA, and NO, inducing angiogenesis (33).…”
Section: Discussionmentioning
confidence: 99%